Prokrastinasi Akademik Ditinjau dari Adversity Quotient dalam Mengerjakan Skripsi pada Mahasiswa - C Christover; Rianda Elvinawanty (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2020)
The study aims to determine the relationship between adversity quotient and academic procrastination. The hypothesisproposed in this study stated that there was a negative relationship between adversity quotient and academic procrastination,assuming the higher quality of adversity quotient and the lower academic procrastination, and conversely the lower quality ofadversity quotient and the higher academic procrastination. Subjects used in this study were Student of STIE Eka PrasetyaMedan consisting of 105 people who were selected by using total sampling technique. Data were obtained from a scale tomeasure quality of adversity quotient and academic procrastination. The calculation was performed by means of testingrequirements analysis (assumption test) that consists of a test for normality and linearity. Analysis of the data used wasperformed by Product Moment Analysis through SPSS 20 for Windows. The results of data analysis showed that r = -0,844and p = 0.000 (p <0.05), indicating that there was a negative relationship between adversity quotient and academicprocrastination. The results of this study indicated that the contribution (R 2) given to the quality of adversity quotient toacademic procrastination was 71.2 %, the remaining 28.8 % were affected by other factors not examined. From these resultsit can be concluded that the hypothesis is acceptable.